ScaphoLunate Axis Method - Yao, Jeffrey; Zlotolow, Dan A.; Lee, Steve K. (Journal of Wrist Surgery, 2016)
Background Treating chronic scapholunate ligament injuries without the presence of arthritis remains an unsolved clinical problem facing wrist surgeons. This article highlights a technique for reconstructing the scapholunate ligament using novel fixation, the ScaphoLunate Axis Method (SLAM).Materials and Methods In a preliminary review of the early experience of this technique, 13 patients were evaluated following scapholunate ligament reconstruction utilizing the SLAM technique.Description of Techinque The scapholunate interval is reconstructed utilizing a palmaris longus autograft passed between the scaphoid and lunate along the axis of rotation in the sagittal plane. It is secured in the lunate using a graft anchor and in the scaphoid utilizing an interference screw. The remaining graft is passed dorsally to reconstruct the dorsal scapholunate ligament.Results At an average follow-up of 11 months, the mean postoperative scapholunate gap was 2.1 mm. The mean postoperative scapholunate angle was 59 degrees. The mean postoperative wrist flexion and extension was 45 and 56 degrees, respectively. The mean grip strength was 24.9 kg, or 62% of the contralateral side. The mean pain score (VAS) was 1.7. There was 1 failure with recurrence of the pathologic scapholunate gap and the onset of pain.Conclusion While chronic scapholunate ligament instability remains an unsolved problem facing wrist surgeons, newer techniques are directed toward restoring the normal relationships of the scaphoid and lunate in both the coronal and sagittal planes. The SLAM technique has demonstrated promise in preliminary clinical studies.
Keywords: scapholunate; ligament; scapholunate ligament; scapholunate axis method